The history of Arabia and their religious beliefs In the poetry of the great nest (Journal of the College of Basic Education, 2023)
The great dinner Maymoon bin Qais; A pristine poet, the Arabs' soothsayer, and a wanderer of the horizons of the island, he may have been correctly described as the historian of pre-Islamic poets.In his poetry, the history of the Arabs and its events were gathered together. He mentioned the extinct tribes and some of the prophets, recording the Arabs' faith in God, Lord of the Worlds, passing through their religions and customary beliefs prevailing among them.In addition to experiencing the path of his tribe in particular and society in general, he is affected by their intertwined relationships internally and externally, including sermons and lessons as his goals, seeking reform.